THE EVALUATION OF THE EFFECT OF VARIOUS MOUTH RINSE ON THE DISCOLORATION OF DIFFERENT COMPOSITE RESINS - James, Vandana; Balagopal, Sundaresan; I, Vaishnavi .; Varghese, Sunil Chandy; J, Varshinee G.; V, Manishaa. (Journal of Biomedical and Pharmaceutical Research, 2019)
AIM: To determine the effect of various types of mouthrinse on the color stability of the composite resin materials. MATERIALS AND METHODS:  4 types of resin material were chosen and immersed in 4 different types of mouthrinses for 2 mins daily and then restored in artificial saliva for rest of the time for 3 months. The baseline color values and post immersion color values were evaluated using colorimetrics. RESULTS:   All the resin material underwent discoloration. The lowest discoloration was seen during the usage of amflor mouthrinse. The lowest discoloration among the resin material was seen there in nanofill resin material. CONCLUSIONS: From this study we can conclude that mouth rinses with low pH are more detrimental. It’s the filler material matrix that plays a key role on the color stability of the material. KEYWORDS: aesthetic dentistry, discoloration ,  mouthrinse.